Death receptor (DR4) haplotypes are associated with increased susceptibility of gallbladder carcinoma in north Indian population. - Rajani Rai; Kiran L Sharma; Surbhi Sharma; Sanjeev Misra; Ashok Kumar; Balraj Mittal (PLoS ONE)
Background and aim Defective apoptosis is a hallmark of cancer development and progression. Death receptors (DR4, FAS) and their ligands (TRAIL, FASL) are thought to mediate the major extrinsic apoptotic pathway in the cell. SNPs in these genes may lead to defective apoptosis. Hence, the present study aimed to investigate the association of functional SNPs of DR4 (rs20575, rs20576 and rs6557634), FAS (rs2234767) and FASL (rs763110) with gallbladder cancer (GBC) risk. Methods This case-control study included 400 GBC and 246 healthy controls (HC). Genotyping was carried out by Taqman genotyping assays. Statistical analysis was performed by using SPSS ver16. Meta-analysis was performed using Comprehensive Meta-analysis software (Version 2.0, BIOSTAT, Englewood, NJ) to systematically summarize the possible association of SNP with cancer risk. Functional prediction of these variants was carried out using Bioinformatics tools (FAST-SNP, F-SNP). False discovery rate (FDR test) was used in multiple comparisons. Results The DR4 C rs20575 A rs20576 A rs6557634, G rs20575 A rs20576 G rs6557634 and G rs20575 C rs20576 G rs6557634 haplotypes conferred two-fold increased risk for GBC. Among these, the DR4 C rs20575 A rs20576 A rs6557634 haplotype emerged as main factor influencing GBC susceptibility as the risk was not modulated by gender or gallstone stratification. Our meta-analysis results showed significant association of DR4 rs6557634 with overall cancer risk, GI cancers as well as in Caucasians. We didn't find any association of FAS and FASL SNPs with GBC susceptibility. Conclusions The DR4 haplotype C rs20575 A rs20576 A rs6557634 represents an important factor accounting the patients susceptibility to GBC probably due to decreased apoptosis. However, additional well-designed studies with larger sample size focusing on different ethnicities are required to further validate the results.